2016
DOI: 10.1175/bams-d-14-00213.1
|View full text |Cite
|
Sign up to set email alerts
|

CoCoRaHS: The Evolution and Accomplishments of a Volunteer Rain Gauge Network

Abstract: The Community Collaborative Rain, Hail and Snow Network (CoCoRaHS) is a large and growing community of volunteers measuring and reporting precipitation and is making this information broadly available for the research and operational community. CoCoRaHS has evolved through several phases since its beginnings in 1998, first starting as a flood-motivated local Colorado Front Range project, then through a 5-yr nationwide expansion period (2005–09), followed by five years (2010–14) of internal growth and capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 10 publications
1
70
1
1
Order By: Relevance
“…These data showed that rainfall intensity within this storm event was highly spatially varied, highlighting the importance of access to precipitation data with a high spatial resolution for flood management. In recognition of this, research communities have suggested the development of an official volunteer network with the aid of local residents, aimed at routinely collecting rainfall and other meteorological parameters, such as snow and hail (Cifelli et al, ; Elmore et al, ; Reges et al, ). More recent examples include citizen reporting of precipitation type based on their observations (e.g., hail, rain, drizzle, etc.)…”
Section: Review Of Crowdsourcing Data Acquisition Methods Usedmentioning
confidence: 99%
“…These data showed that rainfall intensity within this storm event was highly spatially varied, highlighting the importance of access to precipitation data with a high spatial resolution for flood management. In recognition of this, research communities have suggested the development of an official volunteer network with the aid of local residents, aimed at routinely collecting rainfall and other meteorological parameters, such as snow and hail (Cifelli et al, ; Elmore et al, ; Reges et al, ). More recent examples include citizen reporting of precipitation type based on their observations (e.g., hail, rain, drizzle, etc.)…”
Section: Review Of Crowdsourcing Data Acquisition Methods Usedmentioning
confidence: 99%
“…Furthermore, results demonstrate the issues with analyzing QPE from a single gauge, explaining why the Community Collaborative Rain, Hail, and Snow Network (Kelsch, 1998;Cifelli et al, 2005;Reges et al, 2016) or other densely gauged networks (e.g., the Hydrometeorological Automated Data System, HADS; and the Meteorological Assimilation Data Ingest System, MADIS) tend to be more utilized since results have shown that measurements or qualitycontrolled techniques made by these organizations, especially CoCoRaHS (Community Collaborative Rain, Hail and Snow Network), are significantly more accurate than rain gauges (Simpson et al, 2017), especially for convective events (Moon et al, 2009). …”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the de Vos et al (2017) study highlighted the additional information on the space-time variability of rainfall over a densely populated area that could be retrieved with reasonable accuracy and reliability from such a citizen network. A larger-scale example includes the Community Collaborative Rain, Hail, and Snow Network in the USA, (https://www.cocorahs.org/), which receive approximately 20 000 daily rain-gauge reports from citizen scientists across North America (Reges et al, 2016). In a particularly novel application of exploiting existing networks of data, Rabiei et al (2016) inferred rainfall by utilizing a vehicles GPS location together with sensors attached to the cars windscreen wipers.…”
Section: Mobile Phones and Citizen Sciencementioning
confidence: 99%